Exploring unintended pregnancy journeys among women with psychiatric vulnerability using interpretative phenomenological analysis - Noralie N. Schonewille; Elena Soldati; Monique J.M. van den Eijnden; Nini H. Jonkman; Maria G. van Pampus; Thomas Zoon; Odile A. van den Heuvel; Birit F.P. Broekman (PLoS ONE, 2026)
Background It is known that women with unintended pregnancies (UPs) experience many challenges. Women with psychiatric vulnerability may face specific concerns regarding the transmission of psychiatric vulnerability, parenting skills and bonding capacities with their offspring. This study aimed to explore how women with psychiatric vulnerability experience UPs. Methods This is a prospective qualitative study using semi-structured interviews during pregnancy and after delivery regarding the experiences of women with UPs and psychiatric vulnerability and involved partners. Follow-up interviews were conducted three to six months after delivery. Interpretative phenomenological analysis was employed to analyze the data. Results Women with psychiatric vulnerabilities described unintended pregnancies as complex events, often marked by ambivalent pregnancy intentions, concerns about generational trauma, and fears about parental adequacy. The pregnancies triggered heightened psychiatric symptoms, resurfacing childhood memories, and concerns about stigma, yet also motivated participants to seek support from mental health professionals and trusted others. Women adopted coping strategies such as focusing on the future, seeking distraction, and accepting support to manage emotional challenges. Across pregnancy and postpartum, many participants reported developing strong prenatal and postnatal bonding with the newborn, creating safety nets, and making intentional behavioral changes to support their babies. For several women, the unintended pregnancy ultimately fostered personal growth and contributed to an improvement in mental well-being. Conclusions This study elucidates the experiences of unintended pregnancies in women with psychiatric vulnerability. Our findings show that for women with psychiatric vulnerability, UPs may also become a window of opportunity for treatment, personal growth and create a safety net for the baby and oneself. This work may help mental healthcare providers to support comprehensively expectant parents who decide to continue UPs.